2016
DOI: 10.1097/gox.0000000000000705
|View full text |Cite
|
Sign up to set email alerts
|

Is Sterile Better Than Aseptic? Comparing the Microbiology of Acellular Dermal Matrices

Abstract: Introduction:Postoperative infections are a major complication associated with tissue-expander-based breast reconstruction. The use of acellular dermal matrix (ADM) in this surgery has been identified as a potential reservoir of infection, prompting the development of sterile ADM. Although aseptic and sterile ADMs have been investigated, no study has focused on the occurrence and clinical outcome of bacterial colonization before implantation.Methods:Samples of aseptic AlloDerm, sterile Ready-To-Use AlloDerm, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Several mechanisms have been proposed for how ADMs may lead to infection, including contamination during production, contamination during placement, and seeding from the body postoperatively. When reviewing the results of our previous study investigating microbial growth of ADMs before implantation, 15 we believed that the clinical effect of pre- or perioperative seeding was unlikely. With all culture results failing to show growth, in vivo study was felt to be the next appropriate step.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms have been proposed for how ADMs may lead to infection, including contamination during production, contamination during placement, and seeding from the body postoperatively. When reviewing the results of our previous study investigating microbial growth of ADMs before implantation, 15 we believed that the clinical effect of pre- or perioperative seeding was unlikely. With all culture results failing to show growth, in vivo study was felt to be the next appropriate step.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 In an earlier study performed by our group, we investigated the in vitro effects of sterilization when compared with aseptic processing. 15 A total of 92 samples of ADM were sterilely harvested out of the package before implantation. The samples were taken from both sterile and aseptically processed ADM.…”
Section: Introductionmentioning
confidence: 99%
“…Other published series on AlloDerm RTU, however, have reported higher infection rates, ranging from 6.0% to 25.0%. 15 17 , 19 , 20 Although it is difficult to comment on the disparity in infection rates between studies, we believe that strict adherence to aseptic techniques is critical to minimize the risk, even when using a sterile graft.…”
Section: Discussionmentioning
confidence: 99%
“…176 Some studies have suggested that aseptic processing is more beneficial than sterilisation, but others have found them to be equivalent, and there is currently no consensus on optimal processing. 177,178…”
Section: Discussionmentioning
confidence: 99%